Transcriptomic Analysis of Mycobacterium leprae-Stimulated Response in Peripheral Blood Mononuclear Cells Reveal Potential Biomarkers for Early Diagnosis of Leprosy - Yuan, You-Hua; Liu, Jian; You, Yuan-Gang; Chen, Xiao-Hua; Yuan, Lian-Chao; Wen, Yan; Li, Huan Ying; Zhang, Ying (Frontiers in Cellular and Infection Microbiology, 2021)
We aimed to identify an unique host transcriptional signature in peripheral blood mononuclear cells (PBMCs) in response to Mycobacterium leprae antigens to distinguish between patients with leprosy and non-leprosy controls for early diagnosis of the disease. Sixteen individuals were enrolled in the discovery cohort [eight patients with leprosy, comprising four multibacillary (MB) and four paucibacillary (PB); and eight non-leprosy controls, comprising four healthy house contacts (HHCs) and four endemic controls (ECs)]. The differences in the transcriptome response of PBMCs to M. leprae sonicate antigen were evaluated between leprosy patients and non-leprosy controls, and 12 differentially expressed genes (CCL2/MCP-1, IL-8, JAKM, ATP, ND1, SERP, FLJ10489, LINC00659, LOC34487, LOC101928143, MIR22, and NCF1C) were identified. The accuracy of the 12 differentially expressed genes was further validated for the diagnosis of leprosy using real-time quantitative PCR in 82 individuals (13 MB, 10 PB, 37 HHCs, and 22 ECs) in the validation cohort. We found that a 5 gene signature set IL-8, CCL2/MCP-1, SERP, LINC00659 and FLJ10489 had a suitable performance in discriminating leprosy from ECs. In addition, elevated expression of IL-8, CCL2/MCP-1, SERP and LINC00659 was associated with MB diagnosis compared with ECs, whereas increased expression of IL-8, CCL2/MCP-1, SERP and FLJ10489 was found to be useful biomarkers for PB diagnosis from ECs. Moreover, we found decreased expression of NCF1C among leprosy patients could distinguish leprosy from HHCs, whereas higher expression of CCL2 among MB than PB could distinguish different leprosy patients. In conclusion, among the 12 candidate host genes identified, a three gene signature IL-8, CCL2/MCP-1, and SERP showed the best performance in distinguishing leprosy patients from healthy controls. These findings may have implications for developing a rapid blood-based test for early diagnosis of leprosy.